Understanding the Capacity Utilization Rate and Overcapacity of China’s Coal Industry and Interprovincial Heterogeneity - Yanping Ju; Xinhua Wang (IEEE Access, 2019)
The overcapacity of China's coal industry is mainly caused by the inefficiency of the production processes and the imbalance between market supply and demand (effective supply shortage). Due to the particularity of China's overcapacity, traditional capacity utilization rates do not well represent the real situations of China's overcapacity in coal industry. Based on the differences of production conditions in coal-producing provinces in China, this article quantitatively estimates the coal production capacity utilization rates of 24 coal-producing provinces and regions in China from 2001 to 2016 by using the heterogeneous stochastic frontier analysis method. It Evaluates China's coal industry overcapacity index by introducing a correction factor of the demand-supply ratio, which takes into consideration of the supply-demand imbalance characteristics of Chinese overcapacity. The research findings show that the overall level of capacity utilization in China's coal industry is not high, and regional differences are significant. In addition, it is observed that the production capacity utilization rate is lower in northeast and east China than that in west and central China. Coal capacity utilization rate and its heterogeneity are affected by exogenous variables such as economic development and other variables. The coal overcapacity index has obvious cyclic characteristics, and there are still opportunities for improvement in the western production areas and the provinces with large-scale production capacity.